2007
DOI: 10.1051/0004-6361:20065470
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic braking in young late-type stars

Abstract: Context. The existence of rapidly rotating cool stars in young clusters implies a reduction of angular momentum loss rate for a certain period of the star's early life. Recently, the concentration of magnetic flux near the poles of these stars has been proposed as an alternative mechanism to dynamo saturation in order to explain the saturation of angular momentum loss. Aims. In this work we study the effect of magnetic surface flux distribution on the coronal field topology and angular momentum loss rate. We i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In the course of their evolution, rotation decreases due to the loss of angular momentum with stellar winds and magnetic breaking (Weber & Davis 1967;Jianke & Collier Cameron 1993;Aibéo et al 2007). Thus stellar rotation can be used to estimate stellar ages, and it is well known that solar-type stars follow a law of the form P Rot ∝ t 1/2 (Skumanich 1972).…”
Section: Age From Stellar Rotation: Gyrochronologymentioning
confidence: 99%
“…In the course of their evolution, rotation decreases due to the loss of angular momentum with stellar winds and magnetic breaking (Weber & Davis 1967;Jianke & Collier Cameron 1993;Aibéo et al 2007). Thus stellar rotation can be used to estimate stellar ages, and it is well known that solar-type stars follow a law of the form P Rot ∝ t 1/2 (Skumanich 1972).…”
Section: Age From Stellar Rotation: Gyrochronologymentioning
confidence: 99%
“…In both cases the rotation rate affects the magnetic field distribution. Aibéo et al (2007) have argued that re-distribution of coronal flux in stars does not significantly change the wind efficiency for the magnetic breaking. However, their model took into account only existing magnetic flux with no addition of new emerging flux (i.e.…”
Section: Implications For the Long Term Stellar Evolutionmentioning
confidence: 99%
“…Based on WD's model, a large number of more detailed and complex studies of AML in cool and hot stars, as well as in protostellar accretion disks, have been done both analytically (Mestel 1968;Holzwarth 2005) and numerically (Keppens & Goedbloed 2000;Matt & Pudritz 2008a,b;Ud-Doula et al 2009). In particular, Aibéo et al (2007) have shown that AML can be modified by a factor of 2-4 when introducing magnetic flux at high latitudes. They explain the change in AML as a result of a change in the mass flux or the size of the Alfvén surface, but they argue that the change in the magnetic flux tubes topology should not significantly affect magnetic breaking.…”
Section: Introductionmentioning
confidence: 99%
“…However, the magnetic activity-rotation relation breaks for rapidly rotating stars, where the indicators of stellar magnetism saturate and become independent of rotation. A saturation of the dynamo operating inside the star, inhibiting the increase of magnetism with rotation rate, has been attributed to explain the activity saturation observed in low-period stars (Vilhu 1984), but alternative explanations also exist (e.g., MacGregor & Brenner 1991;Jardine & Unruh 1999;Aibéo, Ferreira & Lima 2007).…”
Section: Introductionmentioning
confidence: 99%